A comprehensive review and analysis on CO2 heat pump water heaters. (August 2022) - Wang, Ji; Belusko, Martin; Evans, Michael; Liu, Ming; Zhao, Chunrong; Bruno, Frank
Highlights: Existing CO2 HPWHs in industrial and residential sectors are reviewed. Performance restricted by the pinch point effect is analyzed. Limitations in CO2 compressors and lubrication are revealed for the first time. Current enhancements to overcome the limitations are summarized. Abstract: In the context of the Montreal Protocol, CO2 is considered as an appropriate natural refrigerant with an Ozone Depletion Potential (ODP) of zero and a Global Warming Potential (GWP) of one. A CO2 heat pump water heater (HPWH) can provide hot water with a relatively high COP and consume significantly less energy than all electric or gas water heaters. This study reviews and analyses the existing CO2 HPWHs both in industrial and residential sectors, where the low-temperature and high-temperature systems are classified by the heat delivery temperature of below and above 80 °C, respectively. The significance and features of existing CO2 HPWHs are also summarised in this study. Moreover, the performance limitations of current CO2 HPWHs are discussed considering the temperature gliding matching, and the technical constraints in both CO2 compressors and heat exchangers. Due to the drastic variation of CO2 heat capacity with temperature and pressure, the heat exchange process between sCO2 and water is affected by the pinch point. The temperature gliding matching can be enhanced by optimising the parameters in both the CO2 and water sides, using zeotropic refrigerant mixtures, or adding new devices or cycles to the existing CO2 system. Another way to improve the system performance is increasing the discharge pressure or discharge temperature, while current CO2 reciprocating compressors have an upper-temperature limit of 140 °C and upper-pressure limit of 140 bar, as well as some constraints in the heat exchangers. Due to the decomposition risk of lubricant in the compressor, two types of oil-free compressors (turbo and scroll) have been described. But it is found that the turbo-compressor is hard to provide a competitive efficiency when the pressure is high, and there is a significant leakage flow in a scroll compressor.